Aplikasi Pupuk Hayati Bakteri Endofitik Penambat N2 dan Pupuk N untuk Meningkatkan Pertumbuhan Tanaman Jagung (zea mays l.) Pada Ultisols Kentrong - Mieke Rochimi Setiawati; Pujawati Suryatmana (Soilrens, 2022)
Corn cultivation on Ultisols is limited due to low nitrogen content of the soil. Efforts to increase the N content in the soil include the use of biofertilizers by symbiotic nitrogen-fixing endophytic bacteria. This study assesed various combination of nitrogen fertilizer doses and N2-fixing endophytic biofertilizer to increase the growth of maize in Ultisols Kentrong. The experiment was conducted at the Ciparanje Experimental Greenhouse, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. A randomized block design was used which consisted of 16 treatments with 3 replications, with a combination of doses of urea fertilizer and endophytic biofertilizer applied to seeds or planting holes. The experimental results showed that the combination of urea fertilizer and biofertilizer doses had a significant effect on the population of endophytic bacteria in the roots and leaves of corn plants, plant wet weight, root dry weight and shoot dry weight, plant height, stem diameter, plant nitrogen uptake and content of plants but was not significantly affected on the number of corn leaves. Combination of 80 kg ha-1 urea fertilizer and 3.6 kg ha-1 of biofertilizer was the best combination which increased the dry weight of the corn plant and reduced the dose of urea fertilizer